The articular manifestations of progressive systemic sclerosis (scleroderma). Issue 2 (April 1982) - Baron, M; Lee, P; Keystone, E C
Abstract : The articular manifestations of progressive systemic sclerosis (PSS) were studied in 38 patients. Of these, 66% experienced joint pain and 61% had signs of joint inflammation. Limitation of joint movement was seen in 45%. Radiological abnormalities included periarticular osteoporosis (42%), joint space narrowing (34%), and erosions (40%). Erosive disease did not correlate with disease duration, presence of rheumatoid factor, antinuclear antibodies, distal tuft resorption, or the extent of the scleroderma skin changes. Calcinosis was seen more frequently in those patients with articular erosions (67%). Erosive osteoarthritis of the distal interphalangeal joints (7 patients) was associated with impaired finger flexion. Joint involvement in PSS occurs frequently and may resemble rheumatoid arthritis in the early stages but is less destructive. The occurrence of unrelated arthropathy, such as primary osteoarthritis, is not uncommon, and its differentiation from true PSS joint disease can be difficult.